Applications of Neuro-marketing for assessing the Customer values: In view to Game Industry - Arshi Naim (Web of Journals Publishing, 2023)
This is an extended research explaining the growth of game industry by the application of neuromarketing to measure the customer’s values. Neuromarketing is the application of neuroscience that built the understanding of consumer preferences toward products and services. It explains the neural activity connected with preference and purchase objective. This research focuses on application of neuromarketing for measuring consumer’s emotions for video games. Various physiological measurement techniques have been proposed to facilitate the recording of this crucial aspect of the decision-making process, including brain imaging techniques, functional magnetic resonance imaging (fMRI), electroencephalography (EEG), steady state topography (SST)], and various biometric sensors. EEG detects the sequential changes of brain activity, without appreciable time delay it is needed to assess both the unconscious reaction and sensory reaction of the customer.
Keywords: Neuromarketing; Consumer Preferences; Brain Imaging Techniques; Functional Magnetic Resonance Imaging; Electroencephalography; Steady State Topography; Biometric Sensors